Dual Hypervalent Iodine(III) Reagents and Photoredox Catalysis Enable Decarboxylative Ynonylation under Mild Conditions1. (26th May 2015) - Huang, Hanchu; Zhang, Guojin; Chen, Yiyun
Abstract A combination of hypervalent iodine(III) reagents (HIR) and photoredox catalysis with visible light has enabled chemoselective decarboxylative ynonylation to construct ynones, ynamides, and ynoates. This ynonylation occurs effectively under mild reaction conditions at room temperature and on substrates with various sensitive and reactive functional groups. The reaction represents the first HIR/photoredox dual catalysis to form acyl radicals from α‐ketoacids, followed by an unprecedented acyl radical addition to HIR‐bound alkynes. Its efficient construction of an mGlu5 receptor inhibitor under neutral aqueous conditions suggests future visible‐light‐induced biological applications.